Effect of breastfeeding promotion interventions on child growth: a systematic review and meta‐analysis. (December 2015) - Giugliani, Elsa R.J.; Horta, Bernardo L.; Loret de Mola, Christian; Lisboa, Bernardo O.; Victora, Cesar G.
Abstract: Aim: To update a previous systematic review and meta‐analyses about the effect of breastfeeding promotion interventions on child growth. Methods: Studies evaluating the effect of any type of breastfeeding promotion intervention on child weight, length (or height) and weight/height (or BMI) were screened. Papers published between 2006 and 2014 were checked using the following databases: PubMed/MEDLINE, Embase, Cochrane Database of Systematic Reviews, Lilacs and SciELO. Results: Sixteen studies were added to 19 other studies identified in the previous review, resulting in 35 studies. Meta‐analyses of studies reporting on mean weight, length, weight/length or BMI showed that the interventions had no impact on weight or length/height z scores [pooled effect: 0.03 (95% confidence interval: −0.06;0.12) and 0.03 (95% confidence interval: −0.02;0.08), respectively] and had a modest, but significant, reduction in body mass index/weight‐for‐height z scores [z score mean difference: −0.06 (95% confidence interval: −0.12;0.00)], which was limited to studies from low‐ and high‐incomes settings. For all three outcomes, there was important heterogeneity among studies, which should be taken into account when interpreting the results. Conclusion: Breastfeeding promotion interventions were not associated with significant changes in weight or length, but led to a modest, albeit significant, reduction in body mass index/weight‐for‐height z scores.